The National COVID‐19 Clinical Evidence Taskforce: pregnancy and perinatal guidelines. (2nd October 2022) - Homer, Caroline SE; Roach, Vijay; Cusack, Leila; Giles, Michelle L; Whitehead, Clare; Burton, Wendy; Downton, Teena; Gleeson, Glenda; Gordon, Adrienne; Hose, Karen; Hunt, Jenny; Kitschke, Jackie; et al.
Abstract: Introduction: Pregnant women are at higher risk of severe illness from coronavirus disease 2019 (COVID‐19) than non‐pregnant women of a similar age. Early in the COVID‐19 pandemic, it was clear that evidenced‐based guidance was needed, and that it would need to be updated rapidly. The National COVID‐19 Clinical Evidence Taskforce provided a resource to guide care for people with COVID‐19, including during pregnancy. Care for pregnant and breastfeeding women and their babies was included as a priority when the Taskforce was set up, with a Pregnancy and Perinatal Care Panel convened to guide clinical practice. Main recommendations: As of May 2022, the Taskforce has made seven specific recommendations on care for pregnant women and those who have recently given birth. This includes supporting usual practices for the mode of birth, umbilical cord clamping, skin‐to‐skin contact, breastfeeding, rooming‐in, and using antenatal corticosteroids and magnesium sulfate as clinically indicated. There are 11 recommendations for COVID‐19‐specific treatments, including conditional recommendations for using remdesivir, tocilizumab and sotrovimab. Finally, there are recommendations not to use several disease‐modifying treatments for the treatment of COVID‐19, including hydroxychloroquine and ivermectin. The recommendations are continually updated to reflect new evidence, and the most up‐to‐date guidance is available online (https://covid19evidence.net.au ). Changes in management resulting from the guidelines: The National COVID‐19 Clinical Evidence Taskforce has been a critical component of the infrastructure to support Australian maternity care providers during the COVID‐19 pandemic. The Taskforce has shown that a rapid living guidelines approach is feasible and acceptable.